Economic justification of enterprise's business decisions during the implementation of innovative startup projects - Havrys, Olha; Maistro, Ruslana; Lynnyk, Olena (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article discusses some aspects of the current development of innovative entrepreneurship and the economic justification at enterprises of business decisions on the implementation of start-up projects. It is emphasized that various upheavals, including the military actions that Ukraine is currently experiencing, social conflicts, ecological cataclysms can stop the development of the economyof any country or push it back, and the driving forces of the modern economy are intelligence, knowledge and new ideas. It has been proven that there is a positive trend in the development of technological entrepreneurship through start-up activities and its impact on progress in Industry 4.0.The analysis of scientific sources showed that the geography of research on innovative startup projects is very broad and covers almost all continents and most countries of theworld, but the topic is so relevant andmultifaceted that it requires further scientific development. У статті розглянуто деякі аспекти сучасного розвитку інноваційного підприємництва та економічного обґрунтування на підприємствах бізнес рішень стосовно реалізації стартап проектів. Наголошується, що різні потрясіння, в тому числі військові дії, які зараз переживає Україна, соціальні конфлікти, екологічні катаклізми можуть зупинити розвиток економіки будь-якої країни або відкинути її назад, а рушійними силами сучасної економіки є інтелект, знання та нові ідеї. Було доведено, що існує позитивна тенденція розвитку технологічного підприємництва через стартап діяльність та її вплив на прогрес в Індустрії 4.0. Аналіз наукових джерел показав, що географія досліджень інноваційних стартап-проектів дуже широка і охоплює практично всі континенти та більшість країн світу, але тема настільки актуальна та багатогранна, що потребує подальшої наукової розробки.
Економічне обґрунтування бізнес-рішень підприємства під час реалізації інноваційних стартап-проектів
Keywords: innovative entrepreneurship; start-up projects; justification of business decisions; risks; profitability; investment; інноваційне підприємництво; стартап проекти; обґрунтування господарських рішень; ризики; прибутковість; інвестиції